2016
DOI: 10.1111/and.12614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental left varicocele repair on hypoxia-inducible factor-1α and vascular endothelial growth factor expressions and angiogenesis in rat testis

Abstract: This study was aimed to investigate the effects of experimental left varicocele (ELV) repair on hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) expressions and angiogenesis in rat testis. ELVs were surgically created in 26 adult male Sprague-Dawley rats. Thirty days after surgery, ELV repair was performed in 13 of the rats. All rats subsequently underwent orchiectomy 30 days after the last laparotomy. Histology of ELV-repaired testicles was compared to that of the unrepaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…On the other hand, the levels of pO 2 were negatively related with levels of HIF-1 alpha and Ki67 but positively related with the levels of CK20. Previous study showed that the expression of cytokeratin was enhanced in the cells with low oxygen tension [10], suggesting that different CK may have different functions. In this sense, low pO 2 could affect the activities of biomarkers of CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the levels of pO 2 were negatively related with levels of HIF-1 alpha and Ki67 but positively related with the levels of CK20. Previous study showed that the expression of cytokeratin was enhanced in the cells with low oxygen tension [10], suggesting that different CK may have different functions. In this sense, low pO 2 could affect the activities of biomarkers of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 alpha is oxygen-mediated factor, which affects HIF bioactivity. HIF-1 alpha can activate genes and their translated proteins, such as erythropoietin [8], glucose transporters [9], and vascular endothelial growth factor (VEGF) [10]. The change for HIF-1 alpha has been detected in colorectal cancer (CRC) [11, 12] and several authors have described its importance in angiogenesis and CRC growth [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in testicular MDA level (a) and SOD activity (b) in different groups. The supply of oxygen decreases in varicocele as a result of venous stasis(Goren et al, 2017) which can increase ROS production and expression of pro-apoptotic proteins such as caspases(Bayomy, Sarhan, & Abdel-Razek, 2012), Bax, and ***p < .001 significant differences versus Sham group.…”
mentioning
confidence: 99%
“…Several reports including Azizi et al have demonstrated the protective effects of NaHS against oxidative stress in ischaemia-reperfusion-induced acute kidney injury in rats (Azizi, Seifi, Kadkhodaee, & Ahghari, 2016).Hypoxia is another factor which causes deleterious effects on sperm quality such as vacuolisation and reduction of sertoli, spermatogonia and leydig cells. The supply of oxygen decreases in varicocele as a result of venous stasis(Goren et al, 2017) which can increase ROS production and expression of pro-apoptotic proteins such as caspases(Bayomy, Sarhan, & Abdel-Razek, 2012), Bax, and…”
mentioning
confidence: 99%
“…38,39 Hypoxia In rats, the expression of hypoxia inducible factor is elevated in the presence of a varicocele and subsequently decreases with repair. 40,41 It is postulated that stasis of blood could affect partial oxygen pressure and metabolism in the testis. 42 Renal and adrenal reflux…”
Section: Proposed Mechanism Detailsmentioning
confidence: 99%